Experimental Optimization and Modeling of Supercritical Fluid Extraction of Oil from Pinus gerardiana. Issue 4 (22nd February 2021) - Amani, Mitra; Ardestani, Nedasadat Saadati; Honarvar, Bizhan
Abstract: The influence of different temperatures, pressures, and flow rates on the supercritical fluid extraction (SFE) of oil from Pinus gerardiana was investigated. Extraction was designed using the Box‐Behnken design and artificial neural network. Furthermore, a mathematical model of broken and intact cells was applied to consider mass transfer kinetics of extracted natural materials. The experimental oil extraction was performed by Soxhlet and supercritical carbon dioxide methods and the yield and composition of the obtained oils was compared. Although the yield of the SFE process was lower than that of the Soxhlet extraction, the SFE presented the advantage of shorter extraction time and lower temperatures. Also, the chemical compositions of the obtained oils from Soxhlet and SFE processes were the same. Abstract : Supercritical CO2 was applied to extract oil of Pinus gerardiana seeds for the first time. Supercritical extraction was performed under different temperatures, pressures, and flow rates. The yield and composition of the oils obtained by Soxhlet extraction and supercritical fluid extraction were compared. A mathematical model of broken and intact cells helped to evaluate the mass transfer kinetics.